Transporte de vapor de água e sorção de CO2 em filmes de polisulfona: efeito das variáveis de processamento e envelhecimento físico - Ouriques, Hellen Rose Catão (Universidade Federal de São Carlos, 2004)
Water vapor transport properties and CO2 sorption were studied for bisphenol A Polysulfone films, PSF, prepared with different thickness via solvent casting and a compression molding. From the measurements of water vapor transport for Polysulfone films with different thickness and methodologies of processing; solvent casting controlling the cooling and the evaporation rates and compression molding, it was possible to identify the Polysulfone films may be constituted of different phases and shows distinct permeability values. In addition, this model made possible the characterization and quantification of the existence of an area corresponding to the fraction of frozen holes, and from the correlation of this area with permeability, was possible to propose a graphical representation that shows the existence of a limit area of frozen holes corresponding to 0,042 cm2. This area was interpreted as the limiting value; below it is possible obtain Polysulfone film with permeability magnitudes values of (1,56±0,30)X10-13 g.mmHg-1.cm-1.s-1, independently of the type of processing used, and the correspondent transport mechanism predominantly followed Henry s Law. Otherwise, above the limit area value of frozen holes the Polysulfone films showed selective characteristics. The CO2 sorption results were analyzed based on the interpretation of the observations produced by a two level factorial design, 23, performed to evaluate in two levels three factors of thermal treatment used to accelerated physical ageing of Polysulfone films. The interpretation of these results were done by a cubic geometric representation of the factors, and corroborated with the results obtained for the water transport indicating that Polysulfone films, independently of the chemical nature of the penetrant used, there was a tendency of CO2 condensation or water clustering formation, by hydrogen bonding. This phenomena was observed in both cases since without changing the original polymer film s morphology obtained by different processes. The global analysis of the obtained results for both penetrants leads to the same conclusions. However, considering the chains rigidity and the high glass transition temperature of the Polysulfone, the water vapor permeability and sorption of CO2 on the amorphous glassy state have strong dependence with the area of frozen holes.
Keywords: Físico-química; Transporte de vapor de água; Sorção de CO2; Envelhecimento físico; Otimização multivariada; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA